Artificial Intelligence Project Management Methodologies: Insights from Field Experts in Saudi Arabia - Walaa Alsumari; Omer Alrwais (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2025)
This study investigates the impact of project management (PM) methodologies on Artificial Intelligence (AI) project execution in Saudi Arabia, while addressing global AI PM challenges. Utilizing an exploratory approach combining literature reviews, multi-company case studies, and surveys with 31 local AI practitioners, this research analyzes operational workflows. Locally, Agile dominates, being applied in 60% of projects primarily focused on applied AI. Globally, projects grapple with unclear leadership, role ambiguity, inconsistent hybrid setups, and non-linear risks. These insights highlight the critical need for purpose-built frameworks tailored to AI’s inherent complexity, technical uncertainty, and ethical demands, paving the way for optimized regional AI initiatives.